Synthesis and characterization of a new photoinduced switchable β-cyclodextrin dimer - Hamon, Florian; Blaszkiewicz, Claire; Buchotte, Marie; Banaszak-Léonard, Estelle; Bricout, Hervé; Tilloy, Sébastien; Monflier, Eric; Cézard, Christine; Bouteiller, Laurent; Len, Christophe; Djedaini-Pilard, Florence (Beilstein Journal of Organic Chemistry, 2014)
This paper reports an efficient preparation of bridged bis-β-CD AZO-CDim 1 bearing azobenzene as a linker and exhibiting high solubility in water. The photoisomerization properties were studied by UV–vis and HPLC and supported by ab initio calculations. The cis/trans ratio of AZO-CDim 1 is 7:93 without irradiation and 37:63 after 120 min of irradiation at 365 nm; the reaction is reversible after irradiation at 254 nm. The photoinduced, switchable binding behavior of AZO-CDim 1 was evaluated by ITC, NMR and molecular modeling in the presence of a ditopic adamantyl guest. The results indicate that AZO-CDim 1 can form two different inclusion complexes with an adamantyl dimer depending on its photoinduced isomers. Both cavities of cis-AZO-CDim 1 are complexed simultaneously by two adamantyl units of the guest forming a 1:1 complex while trans-AZO-CDim 1 seems to lead to the formation of supramolecular polymers with an n:n stoichiometry.
Keywords: azobenzene; cyclodextrins; inclusion complex; photoisomerization; switchable binding behavior

(untitled) - Hedges, A. R. (Chem. Rev., 1998)

Cyclodextrins and their complexes - Dodziuk, H. (Wiley-VCH, 2006)

Cyclodextrins in Pharmaceutics, Cosmetics and Biomedicine - Bilensoy, E. (John Wiley & Sons, Inc., 2011)

(untitled) - Hirayama, F.; Uekama, K. (Adv. Drug Delivery Rev., 1999)

(untitled) - Uekama, K.; Hirayama, F.; Irie, T. (Chem. Rev., 1998)

(untitled) - Loftsson, T.; Brewster, M. E. (J. Pharm. Pharmacol., 2010)

(untitled) - Hicks, K. B.; Haines, R. M.; Tong, C. B. S.; Sapers, G. M.; El-Atawy, Y.; Irwin, P. L.; Seib, P. A. (J. Agric. Food Chem., 1996)

(untitled) - Shaw, P. E.; Wilson, C. W. (J. Food Sci., 1983)

(untitled) - Liu, Y.; Chen, Y. (Acc. Chem. Res., 2006)

(untitled) - Harada, T.; Pham, D.-T.; Leung, M. H. M.; Ngo, H. T.; Lincoln, S. F.; Easton, C. J.; Kee, T. W. (J. Phys. Chem. B, 2011)

(untitled) - Liu, Y.; Chen, Y.; Liu, S.-X.; Guan, X.-D.; Wada, T.; Inoue, Y. (Org. Lett., 2001)

(untitled) - Wilson, D.; Perlson, L.; Breslow, R. (Bioorg. Med. Chem., 2003)

(untitled) - Fujita, K.; Ejima, S.; Imoto, T. (J. Chem. Soc., Chem. Commun., 1984)

(untitled) - Sikorski, C. T.; Petter, R. C. (Tetrahedron Lett., 1994)

(untitled) - Breslow, R.; Zhang, B. (J. Am. Chem. Soc., 1996)

(untitled) - Edwards, W. B.; Reichert, D. E.; d'Avignon, D. A.; Welch, M. J. (Chem. Commun., 2001)

(untitled) - Charbonnier, F.; Marsura, A.; Pintér, I. (Tetrahedron Lett., 1999)

(untitled) - Porwanski, S.; Kryczka, B.; Marsura, A. (Tetrahedron Lett., 2002)

(untitled) - Cieslinski, M. M.; Clements, P.; May, B. L.; Easton, C. J.; Lincoln, S. F. (J. Chem. Soc., Perkin Trans. 2, 2002)

(untitled) - Mourer, M.; Hapiot, F.; Monflier, E.; Menuel, S. (Tetrahedron, 2008)

(untitled) - Hamon, F.; Djedaini-Pilard, F.; Barbot, F.; Len, C. (Tetrahedron, 2009)

(untitled) - Merino, E.; Ribagorda, M. (Beilstein J. Org. Chem., 2012)

(untitled) - Dugave, C.; Demange, L. (Chem. Rev., 2003)

(untitled) - Takashima, Y.; Nakayama, T.; Miyauchi, M.; Kawaguchi, Y.; Yamaguchi, H.; Harada, A. (Chem. Lett., 2004)

(untitled) - Qu, D.-H.; Wang, G.-C.; Ren, J.; Tian, H. (Org. Lett., 2004)

(untitled) - Blaszkiewicz, C.; Bricout, H.; Léonard, E.; Len, C.; Landy, D.; Cézard, C.; Djedaïni-Pilard, F.; Monflier, E.; Tilloy, S. (Chem. Commun., 2013)

(untitled) - Liu, Y.; Kang, S.; Chen, Y.; Yang, Y.-W.; Huskens, J. (J. Inclusion Phenom. Macrocyclic Chem., 2006)

(untitled) - Aoyagi, T.; Ueno, A.; Fukushima, M.; Osa, T. (Macromol. Rapid Commun., 1998)

(untitled) - Casas-Solvas, J. M.; Maros-Maldonado, M. C.; Vargas-Berenguel, A. (Tetrahedron, 2008)

(untitled) - Mukherjee, P. S.; Das, N.; Kryschenko, Y. K.; Arif, A. M.; Stang, P. J. (J. Am. Chem. Soc., 2004)

(untitled) - Angelova, A.; Fajolles, C.; Hocquelet, C.; Djedaïni-Pilard, F.; Lesieur, S.; Bonnet, V.; Perly, B.; Lebas, G.; Mauclaire, L. (J. Colloid Interface Sci., 2008)
And references therein.

(untitled) - Basheer, M. C.; Oka, Y.; Mathews, M.; Tamaoki, N. (Chem. – Eur. J., 2010)

(untitled) - Koshima, H.; Ojima, N.; Uchimoto, H. (J. Am. Chem. Soc., 2009)

Photochemistry and Photophysics - Raul, H. (CRC Press, 1990)

(untitled) - Kauscher, U.; Ravoo, B. J. (Beilstein J. Org. Chem., 2012)

(untitled) - Soto Tellini, V. H.; Jover, A.; Garcia, J. C.; Galantini, L.; Meijide, F.; Vasquez Tato, J. (J. Am. Chem. Soc., 2006)

(untitled) - Bouchemal, K.; Mazzafero, S. (Drug Discovery Today, 2012)
And references therein.

(untitled) - Hamon, F.; Violeau, B.; Turpin, F.; Bellot, M.; Bouteiller, L.; Djedaïni-Pilard, F.; Len, C. (Synlett, 2009)

(untitled) - Carrazana, J.; Jover, A.; Meijide, F.; Soto, V. H.; Vázquez Tato, J. (J. Phys. Chem. B, 2005)

(untitled) - Xu, J.; Tan, T.; Kenne, L.; Sandström, C. (New J. Chem., 2009)

(untitled) - Breslow, R. (Supramol. Chem., 1993)

(untitled) - Zhang, B.; Breslow, R. (J. Am. Chem. Soc., 1993)

(untitled) - Yang, Y.; Zhang, Y.-M.; Chen, Y.; Zhao, D.; Chen, J.-T.; Liu, Y. (Chem. – Eur. J., 2012)

(untitled) - Takashima, Y.; Osaki, M.; Ishimaru, Y.; Yamaguchi, H.; Harada, A. (Angew. Chem., Int. Ed., 2011)
And references therein.

(untitled) - Cézard, C.; Trivelli, X.; Aubry, F.; Djedaïni-Pilard, F.; Dupradeau, F.-Y. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Dupradeau, F.-Y.; Cézard, C.; Lelong, R.; Stanislawiak, E.; Pêcher, J.; Delepine, J. C.; Cieplak, P. (Nucleic Acids Res., 2008)

(untitled) - Dupradeau, F.-Y.; Pigache, A.; Zaffran, T.; Savineau, C.; Lelong, R.; Grivel, N.; Lelong, D.; Rosanski, D.; Cieplak, P. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Vanquelef, E.; Simon, S.; Marquant, G.; Garcia, E.; Klimerak, G.; Delepine, J. C.; Cieplak, P.; Dupradeau, F.-Y. (Nucleic Acids Res., 2011)

AMBER, Version 10 (University of California, 2008)

(untitled) - Jorgensen, W. L.; Chandrasekhar, J.; Madura, J. D.; Impey, R. W.; Klein, M. L. (J. Chem. Phys., 1983)